2020
DOI: 10.3390/nu12020475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Versus Low Carbohydrate Intake in the Morning on Glycemic Variability and Glycemic Control Measured by Continuous Blood Glucose Monitoring in Women with Gestational Diabetes Mellitus—A Randomized Crossover Study

Abstract: Carbohydrate is the macronutrient that has the greatest impact on blood glucose response. Limited data are available on how carbohydrate distribution throughout the day affects blood glucose in women with gestational diabetes mellitus (GDM). We aimed to assess how a high-carbohydrate morning-intake (HCM) versus a low-carbohydrate-morning-intake (LCM), affect glycemic variability and glucose control. In this randomized crossover study continuous glucose monitoring (CGM) was performed in 12 women with diet treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
0
34
0
4
Order By: Relevance
“…Carreiro et al 52 found that receiving dietary consultation can improve the GV of pregnant women with GDM. A study by Rasmussen et al 53 showed that the GV of pregnant women with GDM in the group eating a high-carbon breakfast was significantly higher than that of pregnant women with GDM in the group eating a low-carbon breakfast. Similarly, a small sample study 54 showed that the low-glycemic-load diet significantly reduced the GV index of pregnant women with GDM compared with the high-glycemic-load diet.…”
Section: Controlling Gvmentioning
confidence: 99%
See 1 more Smart Citation
“…Carreiro et al 52 found that receiving dietary consultation can improve the GV of pregnant women with GDM. A study by Rasmussen et al 53 showed that the GV of pregnant women with GDM in the group eating a high-carbon breakfast was significantly higher than that of pregnant women with GDM in the group eating a low-carbon breakfast. Similarly, a small sample study 54 showed that the low-glycemic-load diet significantly reduced the GV index of pregnant women with GDM compared with the high-glycemic-load diet.…”
Section: Controlling Gvmentioning
confidence: 99%
“…50,51 Three studies have shown specifically that dietary control can reduce blood glucose fluctuations in pregnant women with GDM. [52][53][54] Studies also have shown that reducing postprandial hyperglycemia can effectively reduce postprandial hyperglycemia peak. Carreiro et al 52 found that receiving dietary consultation can improve the GV of pregnant women with GDM.…”
Section: Controlling Gvmentioning
confidence: 99%
“…In the same study, insulin resistance (as measured by homeostatic model assessment for insulin resistance (HOMA-IR)) significantly decreased during the period with the high carbohydrate intake in the morning. However, Rasmussen et al also found a higher mean amplitude of glucose excursions and coefficient of variation in the group receiving a high carbohydrate intake in the morning as compared with the low intake [ 31 ]. There is a lack of randomized clinical trials studying whether a high or low carbohydrate intake in the morning is preferential.…”
Section: Carbohydratesmentioning
confidence: 99%
“…While total calories per day were equal between the groups, omission of breakfast was associated with higher postprandial glucose responses after lunch and dinner, which may be mediated by lower glucagon-like peptide 1 and insulin secretion [ 125 ]. Finally, in a within-subject analysis study of women with gestational diabetes mellitus, high carbohydrate morning meals also had higher measures of MAGE but lower mean glucose compared to equicaloric diets that distributed carbohydrates throughout the day [ 126 ].…”
Section: Strategies To Minimize Gvmentioning
confidence: 99%